The use of systems of typical versions in the investigation of appropriation, embezzlement of property or misappropriation of them through abuse of office (theft) - Синчук, О. В. (Theory and practice of jurisprudence, 2016)
Forensic features of appropriation, embezzlement of property or misappropriation of them through abuse of office (theft) are analyzed, the possibility of optimization of activities of the investigator during the investigation of thefts through the use of typical versions’ systems is considered.